Microstructure and Micromechanical Behaviors of Bulk Amorphous Alloy Prepared by Spark Plasma Sintering - Yaqiong Ge; Zexin Chang; Wenxian Wang; Qingling Hou (Archives of Metallurgy and Materials, 2023)
This study aimed to prepare Zr55Cu30Al10Ni5 bulk amorphous alloys by spark plasma sintering of raw amorphous alloy powders and investigate their microstructure and micromechanical behaviors. When the sintering temperature ( Ts) was 675K, which was lower than the glass transition temperature ( Tg) of the material, the sintered sample was almost fully amorphous but the density was lower. However, when Ts was 705K, which was higher than Tg, partial crystallization occurred, but the density was higher. The hardness of the bonding zone of the sintered sample at 675K was 5.291 GPa due to the lower density, which was lower than that at 705K, and the hardness at 705K was 8.836 GPa. The generation of thermodynamically stable intermetallic phases, the hardness, and the elastic modulus of the samples sintered above Tg were higher due to the higher density.